Effectiveness of Extension Agencies: A Case of Cotton Farmers in Akola District of Maharashtra, India - Sajesh, V.K.; Padaria, R.N. (Indian Journal of Extension Education, 2019)
The present study was carried out in Akola block of Akola district of Maharashtra among thirty randomly selected cotton farmers. The purpose was to identify the comparative effectiveness of selected extension agencies viz., Department of Agriculture, KVK, Input agencies and NGOs against selected indicators. Seventeen indicators under seven dimensions namely ‘access’, ‘assurance’, ‘empathy’, ‘reliability’, ‘responsiveness’, ‘tangibility’ and ‘timeliness’ were used for comparison of agencies using Analytical Hierarchy Process (AHP). The comparison of overall effectiveness of the selected agencies showed that input dealers were found to be most effective followed by department of agriculture and KVK. NGO was perceived to be least effective by the farmers.
Keywords: AHP; Comparative effectiveness; Extension agencies